Effect of Co Addition on the Microstructure and Mechanical Properties of an Al-2wt.%Ni Alloy - Soler, Gabriela de Araújo [UNESP]; de Faria, Andre Ono [UNESP]; Borges, Júlia Silva [UNESP]; Vida, Talita [UNESP]; Souza, Renato Chaves; Avila, Julian Arnaldo [UNESP]; Brito, Crystopher [UNESP] (MDPI, 2024)
Aluminium alloys have been one of the leading materials used in aircraft structural components due to their mechanical performance, low density, and different manufacturing and inspection techniques. The mechanical, chemical, and electrical properties of metallic alloys relate to the microstructural arrangement, which depends on the alloying elements and manufacturing parameters. Therefore, this study aims to experimentally develop an Al-2wt.%Ni-0.5wt.%Co alloy as an alternative for aerospace applications, evaluating the main metallurgical aspects influencing mechanical strength. The samples were solidified in brass moulds with four different diameters, allowing four different cooling rates. A statistical analysis of the correlation between microstructural parameters and mechanical properties is proposed to optimise the conditions for obtaining the best mechanical strength. A microstructure with an essentially cellular matrix of the α-Al phase was observed. The tensile strength limit values (σU) of 117 MPa, specific elongation (δ) of 13.8%, and average microhardness of 33 HV were obtained. The Al-2wt.%Ni-0.5wt.%Co alloy exhibits impressive high cycle fatigue performance, with an endurance limit of 91 MPa at 107 cycles, driven by the synergistic effects of Al3Ni for strength and Al9Co2 for enhanced ductility and toughness.
Keywords: Al-Ni-Co alloys; high cycle fatigue; solidification microstructure; tensile strength